Feminism, Intersectionality, and Gender Category: Essential Contributions for Historical Thinking Development - Díez-Bedmar, María del Consuelo (Frontiers in Education, 2022)
The following article inquires how introducing the gender category, feminism theories, and intersectionality into social sciences education, especially regarding historical thinking development, could be key for the construction of a more critical and egalitarian future. The main research problem is knowing how the use of the gender category is included, or not, in the development of historical thinking in pre-service teacher beliefs and how it could condition them when they work on historical and social problems in the classroom. The main objective is to analyze the historical thinking development in pre-service Spanish teacher students and their capacity for constructing critical discourses with a gender perspective. Pre-service teachers of five Spanish universities (of the Primary and Secondary Education Degree) were asked about a report from a digital newspaper version that forces them to use historical thinking and to consider gender stereotypes and prejudices. Their responses were analyzed both qualitatively and quantitatively. The results indicate that pre-service teachers are not able to identify their own gender roles and prejudiced attitudes when they attempt to explain a social problem and they propose solutions, even when they could verify that there was another manner to understand this report. Hence, this research highlights the relevance of implementing feminism, intersectionality, and gender category for historical thinking development since these future teachers need to work around democratic culture competences. By contrast, not including this perspective will lead to them still maintaining historical thinking and democracy configured on hegemonic, heteropatriarchal, sexist, and Eurocentric cultural models.